Case of the month: Right coronary artery dissection following sports‐related blunt trauma - Hobelmann, A (BMJ Group, 2006)
Coronary artery dissection is a rare life‐threatening complication resulting from blunt traumatic injury. Most cases of coronary artery injury, including dissection, involve the left anterior descending artery given its anatomical location relative to the impact. Right coronary artery (RCA) dissection secondary to blunt trauma is a particularly unusual occurrence, and has not previously been reported in the emergency medicine literature. We present a case of RCA dissection following low impact sport‐related blunt chest trauma and discuss the pathophysiology, risk factors, diagnosis and current treatment options.